Influence of EGR3 Transfection on Imaging and Behavior in Rats and Therapeutic Effect of Risperidone in Schizophrenia Model - Li, Guangfei; Han, Xiaowei; Gao, Wenwen; Song, Zeyu; Zhao, Shuai; Sun, Feiyi; Ma, Hong; Cui, Ailing; Tang, Xiaoying; Ma, Guolin (Frontiers in Psychiatry, 2020)
Objectives: Schizophrenia is a kind of neurodevelopmental psychiatric disorder while scientists have not figured out it’s etiology and effective treatment. We injected early growth response gene (EGR3) into bilateral hippocampus to build schizophrenia rat model. Behavioral phenotyping and resting-state functional magnetic resonance imaging (rs-fMRI) were used to analyze the behavioral impact and cerebral alterations of schizophrenia model rats. The efficacy of risperidone therapy was also evaluated in treated group rats. Methods: Thirty-four rats were divided into 4 groups: schizophrenia model group (E group), sham-operation group (FE group), healthy control group (H group) and risperidone therapy group (T group). Open field test and Morris water maze were conducted as behavioral experiments, then we executed rs-fMRI after 4 weeks of EGR3 gene transfection and risperidone treatment. Regional homogeneity (ReHo), amplitude of low-frequency fluctuations (ALFF) and functional connectivity (FC) were used to analyze imaging data. We examined the behavioral and neural activation difference in four groups, the correlations between behavior and imaging results are also considered. Results: EGR3 gene transfection decreased the total moved distance in open field test and the duration in Q5 zone of Morris water maze. The risperidone treatment can reverse the trend and improve the performance of rats in behavioral test. Conclusions: Schizophrenia induced several neural alterations in rat brain in ALFF and ReHo metrics while risperidone can partly reverse these alterations. The results will support later research of schizophrenia and put forward some new views for the treatment of risperidone on neural activation in schizophrenia.